Clinical Insights into Internuclear Ophthalmoplegia: A Case Report - Rahmadiansyah, Muhammad Fadhil; Muhammad Hidayat (HM Publisher, 2023)
Background: Internuclear ophthalmoplegia (INO) is a rare neuro-ophthalmological disorder characterized by impaired horizontal eye movement coordination due to lesion in the medial longitudinal fasciculus. INO commonly results from demyelinating diseases, vascular lesions, or structural brain abnormalities. Case presentation: A 60-year-old male patient presented with diplopia for the past 4 days. He had history of hypertension and diabetes mellitus and “mild” stroke for past years. Clinical examination revealed normal primary gaze, limited medial movement of the left eye, and diplopia in all gaze positions. Hess screen examination demonstrated underaction of the left medial rectus muscle and overaction of the right lateral rectus muscle. The laboratory results an elevated blood sugar level. Brain CT scan revealed multiple infarcts in the right parietal and cerebellar lobes and left parieto-occipital lobe, with evidence of brain atrophy. The patient was diagnosed with INO. Management involved addressing the underlying systemic diseases, namely diabetes and hypertension, in collaboration with internist and neurologist. The patient also received citicoline therapy and underwent regular follow-up. In the third-month follow-up, the patient demonstrated significant improvement, with reduction in diplopia and enhancement in left eye medial movement. Conclusion: This case report highlights the importance of considering INO in patients presenting with diplopia and a history of vascular risk factors. Timely diagnosis and comprehensive management with regular follow-up is crucial to monitor the progress and enhance the patient's quality of life.